Governança e turismo no sítio do Patrimônio Mundial de Brasília-DF, Brasil - CASTRO, Cleber Augusto Trindade (2019)
The World Heritage title and the global political guidelines imply, among other aspects, the indication of the constitution of governance bodies and the adoption of democratisation strategies for the public management of cultural heritage in general, and for public policies of tourist use of that patrimony , in specific. Thus, this work has the general objective of analysing the influences of the World Heritage patrimony of Unesco that Brasília has in the process of elaboration of public policies by the instance of governance of tourism of the Brazilian Federal District. Specific objectives were established: a) to understand the processes of reactivation, structuring and operation of the Tourism Development Council of the Federal District (Condetur-DF); b) to show the groups of social agents represented in Condetur-DF, as well as their principles and strategies of action in this Council; and c) to relate the discussions and decisions of the Condetur-DF with the political guidelines for the public management of the tourist use of the World Heritage of Brasília. The research takes a qualitative approach and was developed from a case study of Condetur-DF. The study was carried out with a survey and analysis of the semantic content of fifty-six minutes that record all the ordinary meetings of this Council from June 2010 to December 2016. For the analyses, the following aspects were considered: 1) the elective process of the members; 2) the balance of representativeness; 3) evaluation of performance and group; 4) dissemination and access to information; 5) partnerships established for policies of tourist use of cultural heritage; 6) observance of the political guidelines for the use of World Heritage tourism; and 7) the continuity of public policies. The research shows that the title of World Heritage is neglected in the process of elaboration of public tourism policies within the scope of the Condetur-DF. In part, due to a restricted view on cultural heritage. Also by the characteristics of the tourism that prevails in Brasilia, with demand predominantly motivated by being the political-administrative capital of the country. In addition, the Condetur-DF constitutes an institutional space mainly composed of representatives of the private sector of mediation tourism, which also understands that the management of the cultural heritage of Brasilia is under the responsibility of organisations exogenous to the Council.